The role of the endoscopic grading of gastric intestinal metaplasia in assessing gastric cancer risk: A systematic review and meta-analysis - Fang, Shuangshuang; Fu, Yuhan; Du, Sijing; Wang, Lin; Qing, Xiangli; Luo, Xiaoying; Song, Gengqing; Yang, Yang; Wei, Wei (Frontiers in Oncology, 2022)
Abstract Background and Aim Patients with gastric intestinal metaplasia (IM) are at increased risk of gastric cancer (GC). The endoscopic grading of gastric intestinal metaplasia (EGGIM) with high-definition endoscopes has shown the potential to facilitate GC risk stratification. However, a comprehensive review and meta-analysis of published articles are lacking. We conducted a meta-analysis to access the value of EGGIM in the assessment of histological IM. Materials Studies were selected from PubMed, Medline, Embase, and Cochrane (last selection, Jun 2022). We extracted relevant data to calculate the accuracy of EGGIM compared with the operative link of gastric intestinal metaplasia (OLGIM) and to calculate pooled odds ratio (OR) with 95% confidence interval (CI) assessing GC risk with different grading. Results Four diagnostic studies and three case-control clinical trials were included in the analysis, which included 665 patients and 738 patients, respectively. Compared with OLGIM III/IV, EGGIM(5-10) had a pooled sensitivity and specificity of 0.92(95%CI 0.86-0.96) and 0.90(95%CI 0.88-0.93), and the area under the curve(AUC) was 0.9702. In assessing early GC, the pooled OR of patients with EGGIM(5-10) was 7.46(95%CI 3.41-16.31) compared with that of EGGIM(0-4). Conclusions EGGIM is highly consistent with OLGIM, and patients with EGGIM(5-10) are at a higher risk for early GC. Some heterogeneity in the current research suggests that we need to carry out more strict control of confounding factors. (Prospero registration number: 248691)